MULTIFUNCTIONAL ECO-RUBFOAM WINS GOLD MEDAL, THREE SPECIAL JURY AWARDS AT EUROINVENT 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
IASI, ROMANIA, 22 May 2016 – The MultiFunctional EcoRubFoam, an innovative product by Universiti Sains Malaysia (USM) lecturer from the School of Material and Mineral Resources Engineering, Professor Dr. Hanafi Ismail, won a gold medal at the 8th European Exhibition of Creativity and Innovation (EUROINVENT 2016) held here from 19 to 21 May 2016.